Geopolitics and the territorialization of soybean production in the State of Paraná - Lima, João Matheus Afinovicz de; Silva, Márcia da; Freitas, Elisa Pinheiro de (Revista Cerrados, 2025)
This article aims to analyze how the expansion of soybean production in the state of Paraná, Brazil transcends local impacts, integrating into global dynamics. In Paraná, the production of commodities is strongly linked to the international market, being influenced by multinational corporations and trade agreements. Geopolitics reveals inequalities in territorial disputes, with large companies and agro-industrial cooperatives dominating vast areas, while small producers and traditional communities face difficulties in maintaining themselves. The study examines the production of commodities and the geopolitics of soybeans in the state, highlighting the role of territorialization, which involves the appropriation and reconfiguration of space by agribusiness stakeholders, driven by infrastructure aimed at exportation. Based on a literature review and data analysis obtained from IPARDES and IBGE, the results indicate that the expansion of soybeans reflects not only the search for new agricultural areas but also global pressures linked to the export of food and biofuels. The construction of roads and ports strengthens the concentration of power in the hands of large corporations, consolidating a “corporate space” that focuses on optimizing the flow of goods. Thus, soybeans in Paraná exemplify the interconnection between territory, territorialization, and geopolitics in the globalized agribusiness.